(untitled) (Proceedings of International Educators Conference, 2024)
This article provides a comprehensive overview of the role of technology in transforming English language education. It discusses various advancements in digital tools and platforms that have revolutionized the teaching and learning of English, including interactive learning platforms, virtual classrooms, digital resources, language learning apps, adaptive learning systems, and digital assessment tools. The article highlights the benefits of using technology in language education, such as personalized instruction, engagement, and accessibility. Overall, it emphasizes the potential of technology to enhance the effectiveness and impact of English language education in the digital age.